MILDEW RESISTANCE LOCUS O Function in Pollen Tube Reception Is Linked to Its Oligomerization and Subcellular Distribution. Issue 1 (19th July 2017) - Jones, Daniel S.; Yuan, Jing; Smith, Benjamin E.; Willoughby, Andrew C.; Kumimoto, Emily L.; Kessler, Sharon A.
Abstract : MLOs can substitute for NORTIA function in pollen tube reception if they localize to a Golgi compartment prior to pollen tube arrival and retain the ability to homooligomerize. Abstract: Sexual reproduction in flowering plants requires communication between synergid cells and a tip-elongating pollen tube (PT ) for the successful delivery of sperm cells to the embryo sac. The reception of the PT relies on signaling within the synergid cell that ultimately leads to the degeneration of the receptive synergid and PT rupture, releasing the sperm cells for double fertilization. In Arabidopsis ( Arabidopsis thaliana ), NORTIA, a member of the MILDEW RESISTANCE LOCUS O (MLO) family of proteins, plays a critical role in the communication processes regulating PT reception. In this study, we determined that MLO function in PT reception is dependent on MLO protein localization into a Golgi-associated compartment before PT arrival, indicating that PT -triggered regulation of the synergid secretory system is important for synergid function during pollination. Additionally, a structure-function analysis revealed that MLO homooligomerization, mediated by the amino-terminal region of the protein, and carboxyl-terminal tail identity both contribute to MLO activity during PT reception.